A Comparative Study of Intramuscular Ketamine and a Combination of Intramuscular Dexmedetomidine and Ketamine as Premedication in Paediatric Anesthesia - Singh, Riya; Pradhan, Barkha (Birat Journal of Health Sciences, 2023)
Introduction: Preoperative anxiety is an issue of concern in paediatric anaesthesia practice. Forceful transfer of children into the operating room can cause long-term psychological trauma. This clinical study compares intramuscular ketamine and a combination of intramuscular dexmedetomidine and ketamine as anaesthetic premedicants in terms of +anxiolysis, sedation and ease of IV cannulation. Objectives: To compare the level of preoperative anxiety, sedation and ease of cannulation following premedication between intramuscular ketamine and a combination of intramuscular dexmedetomidine and ketamine. Methods: Total of 60 patients belonging to American Society of Anaesthesiologists physical status I-II, in the age group of two to ten years, scheduled for elective surgery under general anaesthesia were included in the study; Group A patients received ketamine 3mg/kg body weight while Group B patients received ketamine 2mg/kg body weight and dexmedetomidine 1mcg/kg body weight intramuscular. The outcome variables were sedation score (Richmond Agitation Sedation Scale), IV cannula acceptance (IV cannula Acceptance Score), and parental separation (Separation Score). Results: The groups were comparable in patient characteristics and hemodynamic parameters between the groups. Median (IQR) sedation score at 10 min were -1 (-2—0) and 0(-1—1) (p< 0.001); mean parental separation scores were 3.76± 0.43 and 3.36±0.55 (p< 0.001); IV cannula acceptance score were 3.73±0.44 and 4.53±7.27 (p= 0.001) in Group A and Group B respectively. Conclusion: Combination of dexmedetomidine and ketamine is superior to ketamine alone in terms of sedation at 15 min and ease of IV cannulation but comparable in terms of anxiolysis.